2018
DOI: 10.3389/fpsyg.2018.01854
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Intensity Modulates the Pain Empathy Response: An Event-Related Potentials Study

Abstract: Previous studies have widely reported that competition modulates an individual’s ability to empathize with pain experienced by others. What remains to be clarified, however, is how modulations in the intensity of competition might affect this type of empathy. To investigate this, we first used a Eriksen Flanker task to set different competitive intensity context (high competitive intensity, HCI; medium competitive intensity, MCI; low competitive intensity, LCI). Then we used a recognition task as a competitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 71 publications
2
12
0
Order By: Relevance
“…We found that at the central site, painful stimuli elicited marginally significant smaller N2 amplitudes than neutral stimuli did. This finding is consistent with what other ERP studies found (Fan and Han, 2008 ; Luo et al, 2018a ). Meanwhile, as expected, the N2 differences between pain/neutral stimuli did not differ between the two groups, which suggests that acute social pain does not influence an early empathic response toward the pain of strangers.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We found that at the central site, painful stimuli elicited marginally significant smaller N2 amplitudes than neutral stimuli did. This finding is consistent with what other ERP studies found (Fan and Han, 2008 ; Luo et al, 2018a ). Meanwhile, as expected, the N2 differences between pain/neutral stimuli did not differ between the two groups, which suggests that acute social pain does not influence an early empathic response toward the pain of strangers.…”
Section: Discussionsupporting
confidence: 93%
“…We adopted 60 digital color photographs similar to those used in previous ERP studies (Fan and Han, 2008 ; Luo et al, 2018a ) in the empathy task during the ERP session. The visual stimuli comprised 30 pictures showing hands in painful situations and 30 matching pictures showing hands in neutral situations.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations